Analisis Wacana Kritis Iklan Hari Tanpa Tembakau Sedunia 2020 oleh Kementerian Kesehatan Republik Indonesia - Kezia Stevanie Tanfriana (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2021)
Indonesian Ministry of Health’s posting on Instagram to celebrate World No Tobacco Day 2020 could be categorized as a multimodal discourse to convey a particular message. This research analyzed the messages and ideologies conveyed by the posting with Systemic Functional Linguistic theory by (Halliday & Matthiessen, 2013) for the textual part and multimodality theory by (Kress & van Leeuwen, 2006) for the visual part. By using both theories, the construction of the discourse coherence from the textual and visual parts could be observed. This research found that the posting conveys several ideologies: there is a higher possibility for a man to become a smoker; smoke is a bad thing; electronic media could persuade kids and teenagers to smoke; electronic media could be used to give education about the negative impact of smoking. Ideologies and meanings from each component of the discourse build a coherent piece of information and persuasion for No Tobacco campaign.